Analogies and antinomies in Tamang stories and heroic deeds: Heroes and victors of immemorial battles and/or victims of ancient curses - Brigitte Steinmann (European Bulletin of Himalayan Research)
Are the Tamangs convinced that they are the heroes of their original mythical tales or eternal victims of an unfortunate religious and national history? How can we uncover their answers and their own analyses in the oral treasures of their epic traditions? This semiotic reading questions the Tamangs’ subjectivities and elements of conviction and/or controversy about their own history, as revealed in certain heroic gestures by lamas, singer of tales, shamans and ordinary people.Many of the answers to these existential and institutional questions take a heroic form in certain recitatives sung by the Tamang singer of tales, the tamba: ideas about cosmology and the end of time, unanswered riddles about the origins of heaven and earth, visible and invisible living beings, and tales of controversial alliances between men, gods and demons. But we find other heroic forms in the dramatised evocations of the origins of society, declaimed and performed by lamas based on ancient rnyingmapa religious corpora in which ancestors are the heroes of a story about kings and queens of heaven who lost their throne because of incestuous crimes. As a counterpoint to these stories, the dramas sung by the shamans during their long trance sessions combine epic and religious arguments, placing them at the heart of their incessant battles, both against the hero of the lamas, Guru Rinpoche, and against the demons, the enemies of mankind. Finally, some of the ideas put forward by ordinary people through their stories and secret language support this collective memory woven at the heart of religious and national analogies and antinomies, evoking a backdrop of institutional and political battles.